Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 242751 species occurrences available in GBIF matching the query: { "and" : [ { "not" : { "PublishingCountry" : [ "is Norway" ] } }, "Country is Svalbard and Jan Mayen" ] } The dataset includes 242751 records from 541 constituent datasets: 824 records from Isotope tracer experiment: nematode abundance. 2 records from Happywhale - Sperm Whale in Arctic Ocean. 9 records from Happywhale - Minke Whale in Arctic Ocean. 2 records from Happywhale - Minke Whale in North Atlantic Ocean. 27 records from Planktic foraminifera counts of sediment core V29-219. 43 records from Relative abundance of planktic foraminifer Globigerinita uvula in sediment core PS1243-1. 3047 records from Minor impact of ocean acidification to the structure of an Arctic sediment microbial community. 1 records from Canadian Museum of Nature Fossil Vertebrate Collection. 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 94 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 41 records from Tartu University fossil collections. 625 records from Diatom assamblage in samples from sediment trap OG3. 37 records from Tropicos Specimen Data. 368 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 120 records from Xeno-canto - Bird sounds from around the world. 2 records from Herbarium Horti Botanici Pisani (PI), Sistema Museale di Ateneo, Università di Pisa. 249 records from Algae (S). 13 records from (Table 3) Median biomasses of macrobenthos in surface sediments. 74 records from Total foraminifera counts of multinet M21/4_MSN699. 7 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from Arctic water Metagenome. 9 records from Duke University Herbarium Bryophyte Collection. 56 records from Fishbase. 98 records from Planktic foraminifera counts at CTD station PS55/081-1. 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 327 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core GIK17728-1 (Table 4). 80 records from Total foraminifera counts of multinet M21/4_MSN704. 6 records from Collection Mollusca SMF. 3 records from Asteroidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 54 records from Total foraminifera counts of multinet M21/4_MSN707. 1 records from NSW AVH data. 1 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 335 records from Moscow University Herbarium (MW). 34 records from Total foraminifera counts of multinet M21/4_MSN715. 5 records from Collection Echinodermata - ZMB. 4817 records from Geographically tagged INSDC sequences. 4 records from LACM Vertebrate Collection. 81 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 10 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 8 records from Collection Tunicata SMF. 53 records from Total foraminifera counts of multinet M21/4_MSN713. 239 records from Herbarium of Umeå University (UME). 244 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-911A. 369 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 420 records from Distribution of planktic foraminifera and calculated sea surface temperature of sediment core MSM05/5_712-1. 62 records from Total foraminifera counts of multinet M21/4_MSN700. 98 records from SIO Benthic Invertebrate Collection. 4 records from DAO Herbarium Type Specimens. 232 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23256-1 in the Arctic Ocean. 2102 records from Neptune Deep-Sea Microfossil Occurrence Database. 5 records from Happywhale - Bowhead in Arctic Ocean. 806 records from Distribution of benthic foraminifera on sediment core sediment core PS1290-4. 15 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Vascular Plant Herbarium. 1 records from Clitellata - SMF. 2 records from Universität Salzburg. 1 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 67 records from Total foraminifera counts of multinet M21/5_MSN734. 12 records from Planktic foraminifera assemblage in sediment core GIK23043-3. 144 records from Relative abundance of N. pachyderma sinistral in sediment core PS1243-1. 99 records from Range table from planktonic foraminifers in ODP Hole 151-909C. 7914 records from particle-attached and free-living bacteria kongsfjorden. 112 records from Collection Porifera SMF. 1 records from MfN - Fossil invertebrates IIb. 22 records from University of Tartu Natural History Museum and Botanical Garden Mycological Collections. 110 records from (Table A.05) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (100-150 µm). 1529 records from Diatom assamblage in samples from sediment trap NB6. 2 records from Liochthonius muscorum n. sp. und L. lapponicus (Träg.) (Acari, Oribatei). 110 records from World distribution of the aquatic Oligochaeta. 17 records from Nannofossil abundance of Hole 38-349. 2 records from CAS Ornithology (ORN). 349 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 12 records from Mesoparasitic copepods (Copepoda: Cyclopoida) associated with polychaete worms in European seas. 15 records from Abundance of benthos infauna at station GIK23060-1. 2041 records from Paleobiology Database. 29 records from Range table from ostracoda in ODP Hole 151-911A. 244 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 4 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Coccoliths in sediment core PS1532-9. 3072 records from marine sediment metagenome Metagenome. 148 records from (Table 2) Megafauna density 2002, 2004 and 2007 in the deep-sea observatory AWI-HAUSGARTEN, Fram Strait. 196 records from Masaryk University - Herbarium BRNU. 131 records from Collection Crustacea SMF. 1 records from Happywhale - White-beaked Dolphin in Arctic Ocean. 8 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 1 records from Collection Crustacea ZMG. 226 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 14208 records from Bacterial biogeography of a High Arctic ice cap. 98 records from Abundance of planktic foraminifera at CTD station PS55/078-1. 200 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 801 records from naturgucker. 1 records from Happywhale - Killer Whale in Arctic Ocean. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 141 records from (Table 3a and b) Median biomass of macrobenthos in surface sediments. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 14 records from Abundance of epibenthic echinoderms at seafloor photography station M21/4_250. 16 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 2014 records from iNaturalist Research-grade Observations. 5 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 66 records from WFVZ Bird Collections. 12 records from Collection Aves (bird skins) SMF. 1 records from Canadian Museum of Nature Crustacea Collection. 98 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 2 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 104 records from Planktic foraminifera counts at CTD station PS55/066. 37 records from Abundance of microzooplankton measured on water bottle samples during METEOR cruise M17/1. 2 records from Botany Division, Yale Peabody Museum. 98 records from Abundance of planktic foraminifera at CTD station PS55/081-1. 95 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core GIK23059-2. 4 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 88 records from Planktic foraminifera counts at CTD station PS55/051. 3 records from Happywhale - Blue Whale in North Atlantic Ocean. 2 records from Canadian Museum of Nature Parasite Collection. 5 records from HO AVH data. 1 records from Cladorhiza corallophila sp. nov., a new carnivorous sponge (Cladorhizidae, Demospongiae) living in close association with Lophelia pertusa and Madrepora oculata (Scleractinia). 123 records from Continuous Plankton Recorder Dataset (SAHFOS). 35 records from AMNH Bird Collection. 5 records from Reef Life Survey: Global reef fish dataset. 1 records from MVZ Bird Collection (Arctos). 776 records from (Fig. 4) Benthic foraminiferal flux of sediment core MD99-2305. 29 records from Natural History Museum Rotterdam - Specimens. 713 records from COMARGIS: Information System on Continental Margin Ecosystems. 1 records from Collection Aves (bird skeletons) SMF. 1 records from Australian National Wildlife Collection provider for OZCAM. 45 records from Total foraminifera counts of multinet M21/4_MSN719. 286 records from (Table 1) Abundance of dead benthic foraminifera in surface sediments of the Arctic Ocean. 4 records from A global database for the distributions of crop wild relatives. 53 records from Total foraminifera counts of multinet M21/4_MSN702. 1 records from Tanaidacea (Crustacea: Peracarida) of the northeast Atlantic: Chauliopleona Dojiri and Sieg, 1997 and Saurotipleona n. gen. from the ‘ Atlantic Margin’. 32 records from Range table from ostracoda in ODP Hole 151-910C. 1 records from BMSM Bailey-Matthews National Shell Museum. 7415 records from Invertebrates Collection of the Swedish Museum of Natural History. 12 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 6 records from Collection Hydrozoa - ZMB. 1 records from Happywhale - White-beaked Dolphin in North Atlantic Ocean. 1 records from MAL. 6 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 8 records from MfN - Fossil plants (Paleophytic). 68 records from Lund Museum of Zoology - Insect collections (MZLU). 57 records from Total foraminifera counts of multinet M21/4_MSN718. 28 records from Australian Museum provider for OZCAM. 2 records from Collection Ctenophora SMF. 175 records from (Table 6) Relative abundance of dead foraminifers in surface sediment. 53 records from Plasm bearing foraminifera counts of multinet M21/5_MSN740. 197 records from Radiolaria assemblage in sediment core GIK17722. 16 records from The Lichens Collection at the Botanische Staatssammlung München. 10625 records from Observation.org, Nature data from around the World. 62 records from Total foraminifera counts of multinet M21/4_MSN705. 87 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 14 records from Royal Belgian Institute of Natural Sciences Crustacea collection. 1 records from Taming an ichnotaxonomical Pandora’s box: revision of dendritic and rosetted microborings (ichnofamily: Dendrinidae). 61 records from (Table A.07) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (150-500 µm). 60 records from (Table A.10) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (150-500 µm). 71 records from Collection Crustacea - ZMB. 153 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1909-2. 13 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 66 records from Range table from ostracoda in ODP Hole 151-910D. 3 records from Happywhale - Sei Whale in Arctic Ocean. 302 records from Effects of varying food-availability on ecology and distribution of smallest benthic organisms in sediments of the arctic Fram Strait during POLARSTERN cruise ARK-XV/2. 167 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1243-1. 1 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 13 records from LACM Malacology. 47 records from Charles University Prague - Herbarium PRC. 1 records from Tracking of Arctic tern migrations 2007-2008. 8 records from Relative abundance of Beella megastoma ( >250 µm) in sediment core PS1243-1. 1 records from Catalogue of the type specimens of Pogonophora (Annelida; seu Polychaeta: Siboglinidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 1 records from Morphological review of the order Neelipleona (Collembola) through the redescription of the type species of Acanthoneelidus, Neelides and Neelus. 7 records from Happywhale - Polar Bear in Arctic Ocean. 1 records from MVZ Egg and Nest Collection (Arctos). 220 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-913B. 93 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1243-2. 50 records from Naturalis Biodiversity Center (NL) - Mammalia. 38 records from Herbarium Senckenbergianum (FR) - Fungi. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 58 records from University of Tartu Natural History Museum and Botanical Garden Botanical Collections. 5 records from Taxon occurrence data for the FungalRoot database. 1 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 96 records from Planktic foraminifera counts at CTD station PS55/063. 7 records from CM Birds Collection. 3 records from DMNS Marine Invertebrate Collection (Arctos). 655 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-5. 14 records from Biodiversitätsdatenbank Salzburg. 2 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 288 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-909C. 182 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1243-1. 2 records from Happywhale - Polar Bear in North Atlantic Ocean. 41 records from Total foraminifera counts of multinet M21/4_MSN714. 1 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 35 records from A community genomics investigation of fungal adaptation to cold. 145 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 1 records from Naturalis Biodiversity Center (NL) - Cnidaria. 1 records from Steiermärkisches Landesmuseum Joanneum - Herbarium GJO. 5 records from Canadian Museum of Nature Herbarium. 44 records from Total foraminifera counts of multinet M21/5_MSN736. 1 records from CSIC-Real Jardín Botánico-Colección de Hongos (MA-Fungi). 4 records from NIWA Invertebrate Collection. 3 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 374 records from Meise Botanic Garden Herbarium (BR). 766 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 661 records from Early succession in benthic hard bottom communities in Kongsfjorden, Svalbard - abundance. 1 records from Duke University Herbarium Lichen Collection. 141 records from (Table 2) Occurrence of ostracoda in surface sediments of the Arctic Ocean. 1451 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 151-913B. 3 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from A new species of Menestho Møller, 1842 from the Arctic with remarks on Menestho albula (Fabricius, 1780) (Gastropoda: Heterobranchia: Pyramidellidae). 36 records from Total foraminifera counts of multinet M21/4_MSN717. 40 records from Range table from planktonic foraminifers in ODP Hole 151-910A. 66 records from (Table A.06) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (125-250 µm). 109 records from Dinoflagellate cysts from sediment core PS1295-4. 5 records from University of Vienna, Institute for Botany - Herbarium WU. 34 records from Total foraminifera counts of multinet M21/4_MSN722. 2 records from NYSM Birds. 308 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 287 records from Dinoflagellate cysts from sediment core PS2138-1. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 138 records from Diversity, standing stock and distribution of dead benthic foraminifera suborder groups (Table 4+6). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 218 records from Metabarcoding surveys of the Arctic marine environment. 95 records from Isotope tracer experiment: nematode isotope ratio. 21 records from Coccoliths in sediment core PS1533-3. 3429 records from Botany (UPS). 15 records from Herbarium Berolinense, Berlin (B). 15 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 605 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 475 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 9 records from Naturalis Biodiversity Center (NL) - Pisces. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 6 records from Nemertini - SMF. 1 records from Morphology and systematic position of Cingula tumidula G. O. Sars, 1878 (Gastropoda: Rissoidae). 2 records from Oribatid mites (Acari: Oribatida) recorded from Ireland: Catalogue, historical records, species habitats and geographical distribution, combinations, variations and synonyms. 33 records from NMNH Paleobiology Specimen Records. 159 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 6 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 28090 records from EOD - eBird Observation Dataset. 53 records from Total foraminifera counts of multinet M21/5_MSN735. 75 records from Museum of Comparative Zoology, Harvard University. 323 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 1220 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 9 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 3100 records from Arctic microbiome along Svalbard Cross Shelf transects. 4447 records from (Table 1) Distribution of benthic foraminifera on sediment core PS2837. 28 records from University of Michigan Herbarium. 2385 records from Controls on microalgal community structures in cryoconite holes upon high Arctic glaciers, Svalbard. 165 records from (Table 5) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2138-1. 904 records from Svalbard Targeted Locus (Loci). 3 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 88 records from Abundance of planktic foraminifera at CTD station PS55/051. 492 records from Naturalis Biodiversity Center (NL) - Aves. 409 records from Hexacorallians of the world. 7 records from Planktic foraminifera counts of multinet M21/5_MSN732. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 44 records from Relative abundance of coccosphere-units of sediment core GIK23400-3. 101 records from Oskarshamn herbarium (OHN). 1 records from Fungal Specimens of National Museum of Nature and Science (TNS). 5 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Mycological Herbarium. 1 records from Angelo State Natural History Collections (ASNHC) Bird specimens (Arctos). 14018 records from Spirulina necromass degradartion in arctic marine sediments. 27 records from Relative abundance of planktic foraminifera in sediment core K11. 394 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-908A. 95 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1243-2. 23 records from Collection Aves (spirit preserved) SMF. 620 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 2 records from ECatSym: Electronic World Catalog of Symphyta. 82 records from ZMMU MSU, White Sea Branch. 5 records from Description of new chiactine-bearing sponges provides insights into the higher classification of Calcaronea (Porifera: Calcarea). 39 records from Total foraminifera counts of multinet M21/4_MSN710. 162 records from Distribution of planktic foraminifera of sediment trap OG5. 202 records from Fish Collection NRM. 430 records from (Table 4a) Distribution of benthic foraminifers of sediment core PS2212-3. 10 records from Happywhale - Beluga in Arctic Ocean. 4 records from Royal Belgian Institute of Natural Sciences Rotifera collection. 38 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 5 records from Range table from planktonic foraminifers in ODP Hole 151-912B. 1 records from Collection Bryozoa - ZIM Hamburg. 77 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 70 records from Macaulay Library Audio and Video Collection. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 1 records from Natural History Museum Maastricht (NL) - Herbarium. 131 records from Happywhale - Humpback Whale in North Atlantic Ocean. 3 records from Collection Pantopoda SMF. 1620 records from Aldegondabreen cryoconite Targeted Locus. 40 records from Distribution of planktic foraminifera of sediment core GIK23424-3. 38 records from Plasm bearing foraminifera counts of multinet M21/5_MSN742. 60 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 101 records from Happywhale - Humpback Whale in Arctic Ocean. 455 records from Naturalis Biodiversity Center (NL) - Botany. 80 records from (Table 1) Abundance of live benthic foraminifera in surface sediments of the Arctic Ocean. 139 records from High gene flow in polar cod (Boreogadus saida) from West-Svalbard and the Eurasian Basin - Occurrence Data. 196 records from Size of planktic foraminifera at CTD station PS55/066. 61 records from Algaterra Types. 8 records from Collection Polychaeta - ZSRO. 5 records from Field Museum of Natural History (Botany) Bryophyte Collection. 2 records from Occurrence records of southern African aquatic biodiversity. 14660 records from EBCC Atlas of European Breeding Birds. 2117 records from Fungi (S). 184 records from Size of planktic foraminifera at CTD station PS55/077-1. 63 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-6. 81 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 4 records from Range table from planktonic foraminifers in ODP Hole 151-912C. 1 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 170 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 192 records from Invertebrates excl. Entomology at the Natural History Museum of Denmark. 134 records from NMNH Extant Specimen Records. 80 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 83 records from Planktic foraminifera counts at CTD station PS55/077-1. 10 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from Museums Victoria provider for OZCAM. 1 records from Ichthyology Collection - Royal Ontario Museum. 1 records from SysTax - Zoological Collections. 4544 records from Arctic benthos Targeted Locus (Loci). 92 records from UMZC Zoological Specimens. 1098 records from (Table 2) Distribution of benthic foraminifers of sediment core PS2138-1. 45 records from Abundance of coccosphere-units of sediment core GIK23400-3. 2 records from CMNH Birds Collection. 53 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 3 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 18 records from Lamont-Doherty/LGL/NSF cruises. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 8 records from Re-classification of Lycoriella Frey sensu lato (Diptera, Sciaridae), with description of Trichocoelina gen. n. and twenty new species. 9 records from Planktic foraminifera assemblage in sediment core GIK17725-1. 4070 records from Invertebrate Paleontology Division, Yale Peabody Museum. 1 records from Arizona State University Lichen Herbarium. 70 records from Isotope tracer experiment: meiofauna counts. 1 records from The empidoid flies (Diptera: Empidoidea, exclusive of Dolichopodidae) of the Russian Arctic islands and Svalbard Archipelago. 886 records from PIROP Northwest Atlantic 1965-1992. 185 records from Size of planktic foraminifera at CTD station PS55/051. 6 records from (Table 1) Lipid and organochlorine content in blood of common eiders (Somateria mollissima) in Svalbard. 64 records from Royal Belgian Institute of Natural Sciences Cnidaria collection. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 1 records from UWFC Ichthyology Collection. 214 records from Range table from planktonic foraminifers in ODP Hole 151-911A. 66 records from University of Tartu Natural History Museum and Botanical Garden DNA and Environmental Sample Collections. 30 records from Abundance of benthos infauna at station GIK23043-2. 83 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 3 records from Collection Pisces SMF. 403 records from Microbial eukaryotes in an Arctic under-ice spring bloom north of Svalbard.. 4 records from Happywhale - Walrus in Arctic Ocean. 32 records from Tiroler Landesmuseum Ferdinandeum. 1 records from Collections and observation data National Museum of Natural History Luxembourg. 358 records from Lund Museum of Zoology (MZLU). 232 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 10 records from Natural History Museum, Vienna - Herbarium W. 78 records from Abundance of planktic foraminifera at CTD station PS55/079-1. 5 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 13 records from (Table 2) Median abundances of macrobenthos in surface sediments. 3 records from CANB AVH data. 30 records from Range table from ostracoda in ODP Hole 151-910A. 3 records from Manchester Museum, University of Manchester, Botany Collection. 292 records from Distribution of planktic foraminifera of sediment trap NB6. 42 records from Relative abundance of coccosphere-units of sediment core GIK23424-3. 67 records from Total foraminifera counts of multinet M21/5_MSN740. 603 records from Polish Arctic Marine Programme. 1 records from Cirripedia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 70 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2214-1. 23 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 11 records from Crinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 36 records from The New York Botanical Garden Herbarium (NY). 5 records from Field Museum of Natural History (Botany) Lichen Collection. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 35 records from Coccoliths in sediment core PS1295-4. 4 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Plantae. 15 records from Marine sediment in Arctic Raw sequence reads. 1 records from Dinoflagellate abundance of Hole 38-345. 31 records from Collection Arachnology SMF. 8 records from Collection Porifera - ZMB. 131 records from Planktic foraminifera counts of sediment core V28-56. 158 records from Botanical Museum, Copenhagen, Mycology Herbarium. 252 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 2 records from Geneva Herbarium – General Collection (G). 40 records from Total foraminifera counts of multinet M21/4_MSN721. 9 records from Distribution of planktic foraminifera of sediment core GIK23352-3 at stadium 5.5. 6067 records from CRIS data set. 231 records from Planktic foraminifera counts during POLARSTERN cruise ARK-XIII/2. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 10 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 757 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 261 records from Royal Botanic Garden Edinburgh Herbarium (E). 7 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 1 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 24 records from Range table from planktonic foraminifers in ODP Hole 151-910D. 4 records from Royal BC Museum - Herbarium (V). 16 records from Danish Mycological Society, fungal records database. 7 records from Distribution of planktic foraminifera of sediment core GIK23342-6 at stadium 5.5. 471 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 1 records from United Herbaria of the University and ETH Zurich. 44 records from Plasm bearing foraminifera counts of multinet M21/5_MSN735. 125 records from RBINS DaRWIN. 2054 records from Lund Botanical Museum (LD). 75 records from GalliForm: Galliformes occurrence records from the Indo-Malay and Palaearctic, 1800-2008. 690 records from Natural History Museum (London) Collection Specimens. 49 records from Coccoliths in sediment core PS1535-8. 101 records from Collection Polychaeta SMF. 548 records from Range table from benthic foraminifers in ODP Hole 151-909C. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 260 records from Radiolaria assemblage in sediment core GIK23424-3. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 11 records from Planktic foraminifera assemblage in sediment core GIK23256-1. 1 records from Cnidaria. 5218 records from The CPR Survey. 34 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2157-3. 1 records from Herbarium J Räsänen. 4 records from Institut Mediterrani d'Estudis Avançats: Colección Osteológica de Aves. 554 records from Distribution of benthic foraminifers (dead) in surface sediments (Table 5). 41 records from Total foraminifera counts of multinet M21/4_MSN711. 38 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2140-1. 3 records from Zariquiey Collection. Biological Reference Collections ICM CSIC.. 3 records from Estonian University of Life Sciences Institute of Agricultural and Environmental Sciences Entomological Collection. 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 2 records from Northern Territory Museum and Art Gallery provider for OZCAM. 260 records from Counts of benthos communities in Kongsfjorden in 2009. 1 records from Collection Bryozoa - ZMB. 23 records from Bivalvia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 190 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1244-2. 43 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2143-1. 349 records from Counts of the dead benthic foraminifera assemblage in surface sediments of the North Atlantic. 8 records from (Table 1) Proportion of Toxoplasma gondii seropositive arctic foxes (Alopex lagopus) by age group and geographic area. 1 records from New articulated asteroids (Echinodermata, Asteroidea) and ophiuroids (Echinodermata, Ophiuroidea) from the Late Jurassic (Volgian / Tithonian) of central Spitsbergen. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2212-6. 210 records from Kongsfjorden/Spitsbergen - soft bottom fauna. 2172 records from The fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from Auckland Museum Botany Collection. 850 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 18 records from Herbarium Senckenbergianum (FR). 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 104 records from Abundance of planktic foraminifera at CTD station PS55/066. 35 records from Plasm bearing foraminifera counts of multinet M21/5_MSN736. 2 records from University of Tennessee Bryophyte Herbarium. 327 records from (Fig. 4) Distribution and stable isotope record of foraminifera, and ice-rafted debris sediment core PS1243-1. 146 records from Sizing Ocean Giants. 282 records from Collection Paläobotanik SMB. 3 records from Ascidiacea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 2 records from Palaeozoological Collections (PZ), Swedish Museum of Natural History (NRM). 80 records from Planktic foraminifera counts at CTD station PS55/080-1. 32 records from Royal Belgian Institute of Natural Sciences Mollusc collection. 98 records from Planktic foraminifera counts at CTD station PS55/078-1. 7 records from Collection Cnidaria SMF. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 96 records from Abundance of planktic foraminifera at CTD station PS55/063. 111 records from Happywhale - Blue Whale in Arctic Ocean. 6 records from Happywhale - Bearded Seal in Arctic Ocean. 45 records from Naturalis Biodiversity Center (NL) - Porifera. 29 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 59 records from Total foraminifera counts of multinet M21/5_MSN739. 10 records from Royal Belgian Institute of Natural Sciences Bird collection. 4 records from Collection Echinodermata SMF. 1300 records from Sea ice and seawater Raw sequence reads. 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 1616 records from Epipelagic mesozooplankton distribution and abundance in Southern Ocean Atlantic sector and the North Atlantic and Arctic 1996-2013. 68 records from Total foraminifera counts of multinet M21/4_MSN701. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 38 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 467 records from Naturalis Biodiversity Center (NL) - Mollusca. 6 records from Pl@ntNet automatically identified occurrences. 40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 345 records from Distribution of planktic foraminifera of sediment trap NB7. 17 records from Happywhale - Fin Whale in Arctic Ocean. 2 records from Edaphobase. 1190 records from Temperature shifts simulating secondary oil recovery. 36 records from CAS Ichthyology (ICH). 2 records from Lepidoptera collection of Hannu Saarenmaa. 302 records from (Table 2) Distribution of benthic foraminifers in the > 125 µm fraction in surface sediments from the central Arctic Ocean. 114 records from Distribution of planktonic foraminifera in water profiles from the North Atlantic Ocean. 48 records from Plasm bearing foraminifera counts of multinet M21/5_MSN741. 135 records from Globigerinita spp. in sediment core MSM05/5_712-2. 3 records from LSUMZ Birds Collection. 2 records from University of Vermont, Pringle Herbarium, Algae Collection. 23 records from Abundance of benthos infauna at station GIK23042-2. 7 records from Gastropods from the Late Jurassic - Early Cretaceous seep deposits in Spitsbergen, Svalbard. 344 records from Collection Vermes - ZMB. 569 records from Mosses (S). 1 records from The Ichthyology Collection at the Staatliches Museum für Naturkunde Stuttgart. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 187 records from Size of planktic foraminifera at CTD station PS55/063. 343 records from JNCC seabird distribution and abundance data (all trips) from ESAS database. 982 records from Diatom assamblage in samples from sediment trap OG4. 3 records from Happywhale - Harbor Seal in Arctic Ocean. 178 records from Culture Collection of Cryophilic Algae. 156 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 55 records from Range table from planktonic foraminifers in ODP Hole 151-909A. 20 records from Collection Bryozoa SMF. 5 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1260 records from Herbarium GB, University of Gothenburg. 121 records from Meiobenthic assemblages colonizing artificial soft sediments at 20 m depth in Arctic glacial Kongsfjorden, Spitsbergen, Svalbard - individual number. 32 records from Coccoliths in sediment core GIK23059-2. 15 records from Sipuncula - SMF. 656 records from Phanerogamic Botanical Collections (S). 36 records from Lichens at Herbarium Berolinense, Berlin (B). 6 records from Planktic foraminifera assemblage in sediment core GIK17724-1. 166 records from NaGISA Project. 4 records from Bryozoa distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 1716 records from Uncultered bacterium Targeted Locus (Loci). 3 records from MfN - Fossil plants (Cenophytic). 10 records from DSMZ Prokarya Collection Catalogue. 69 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 643 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1745-5 (Table 8). 68 records from Total foraminifera counts of multinet M21/5_MSN732. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 377 records from Global Lacustrine Diatoms. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 38 records from Distribution of Geodia species in the Atlantic boreo-arctic region. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN739. 50 records from Planktic foraminifera counts of sediment core V28-25. 479 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 192 records from Range table from planktonic foraminifers in ODP Hole 151-910C. 1313 records from Diatom assamblage in samples from sediment trap OG5. 1 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 38 records from Range table from planktonic foraminifers in ODP Hole 151-908A. 441 records from Benthic foraminiferal assemblage in the 125-250 micron fraction of sediment core PS1745-5 (Table 5). 12 records from Herbario, Departamento de Farmacología, Farmacognosia & Botánica, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 43 records from YoNAH Encounter. 461 records from Benthic foraminifera counts of sediment core GIK23342-6. 26 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from Mammals housed at MHNG, Geneva. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 48 records from Total foraminifera counts of multinet M21/5_MSN733. 43 records from Range table from planktonic foraminifers in ODP Hole 151-913A. 52 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2213-4. 49 records from United States National Plant Germplasm System Collection. 64 records from Allied Humpback Whale Catalogue, 1976 - 2003. 21 records from Happywhale - Fin Whale in North Atlantic Ocean. 140 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1906-2. 3 records from Paleobotany Division, Yale Peabody Museum. 142 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 364 records from Range table from benthic foraminifers in ODP Hole 151-910C. 235 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 514 records from Benthic foraminifera counts of sediment core GIK23353-5. 56 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 2 records from Collection Soil Aninmals. 1 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 2 records from Carnet en Ligne. 51 records from Total foraminifera counts of multinet M21/4_MSN712. 19 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 56 records from MEL AVH data. 40 records from Total foraminifera counts of multinet M21/4_MSN716. 2 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 56 records from Total foraminifera counts of multinet M21/5_MSN741. 1 records from Bell Museum bryophytes. 168 records from Zoology (Museum of Evolution - Uppsala). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences